Plasma metabolomics of the time resolved response to Opisthorchis felineus infection in an animal model (golden hamster, Mesocricetus auratus) - Kokova, Daria; Verhoeven, Aswin; Perina, Ekaterina A.; Ivanov, Vladimir V.; Knyazeva, Elena M.; Saltykova, Irina V.; Mayboroda, Oleg A. (PLOS Neglected Tropical Diseases, 2020)
Background Opisthorchiasis is a hepatobiliary disease caused by flukes of the trematode family Opisthorchiidae. Opisthorchiasis can lead to severe hepatobiliary morbidity and is classified as a carcinogenic agent. Here we investigate the time-resolved metabolic response to Opisthorchis felineus infection in an animal model. Methodology Thirty golden hamsters were divided in three groups: severe infection (50 metacercariae/hamster), mild infection (15 metacercariae/hamster) and uninfected (vehicle-PBS) groups. Each group consisted of equal number of male and female animals. Plasma samples were collected one day before the infection and then every two weeks up to week 22 after infection. The samples were subjected to 1H Nuclear Magnetic Resonance (NMR) spectroscopy and multivariate statistical modelling. Principal findings The time-resolved study of the metabolic response to Opisthorchis infection in plasma in the main lines agrees with our previous report on urine data. The response reaches its peak around the 4th week of infection and stabilizes after the 10th week. Yet, unlike the urinary data there is no strong effect of the gender in the data and the intensity of infection is presented in the first two principal components of the PCA model. The main trends of the metabolic response to the infection in blood plasma are the transient depletion of essential amino acids and an increase in lipoprotein and cholesterol concentrations. Conclusions The time resolved metabolic signature of Opisthorchis infection in the hamster’s plasma shows a coherent shift in amino acids and lipid metabolism. Our work provides insight into the metabolic basis of the host response on the helminth infection.